Kajian identitas nasional indonesia: pancasila dan butir-butir pancasila dalam kehidupan bermasyarakat. - andayani, Ayunda salmanita aulia (Maliki Interdisciplinary Journal, 2025)
The national identity of Indonesia is a result of social construction shaped by history, culture, and the noble values of the nation, one of which is manifested through pancasila as the foundation of the state and a guideline for community life. This research aims to explain the role of pancasila in the formation of national identity and the application of its values in the daily lives of the Indonesian people. The method used in this study is descriptive literature, analyzing both primary and secondary sources. The findings of this study indicate that the values of pancasila, such as belief in god, humanity, unity, democracy, and social justice, play a significant role in strengthening social cohesion, building national character, and addressing the challenges of globalization and foreign cultural influences (Faslah, 2024; sutomo et al., 2021). The implementation of pancasila in community life has proven to foster attitudes of tolerance, solidarity, and nationalism, as highlighted in the research by Herawati (2021), which emphasizes the importance of social justice in maintaining social harmony. Additionally, the study by yulianti (2020) in the journal of citizenship education reinforces national identity among the younger generation. Therefore, the consistent application of pancasila values across various aspects of life is key to maintaining the unity and integrity of the Indonesian nation. A synergy between society and the government is essential to internalize these values trough education, public policy, and socio-cultural activities.